Managing Broken Home Students' Emotions Using Reality Counseling Metaphor Techniques - Adilia Puspita Sari; Leny Latifah; Ajeng Intan Nur Rahmawati (Jurnal Bimbingan dan Konseling Terapan, 2023)
One of the integral aspects of being human is emotion, especially when adapting to a new environment. Poor anger management can prevent people from getting to know themselves and socializing with others. This study was conducted to understand the effectiveness of reality counseling metaphor techniques to improve the emotional management of broken home students in SMA Kabupaten Malang. The research design used was single-subject design, A-B-A design with 3 students with broken home backgrounds as research subjects and poor emotional management based on questionnaire results. The instruments used are questionnaires, observations, and metaphorical reality counseling techniques. The results showed that the initial score obtained the average sum of each aspect, indicating a high level of emotion. After being given counseling treatment, the reality of the counselor's situation metaphorical technique showed an improvement in managing emotions. The presence of a line chart to manage emotions. The results of this study showed that reality counseling with metaphorical techniques effectively improved the emotional management of broken home students. In addition, this study was considered successful because the level of change that occurred after receiving the intervention showed a better attitude, in other words, the treatment given was effective which could reduce the emotional feelings of broken-home students.